A Practical Noise Prediction Method for Cavitating Marine Propellers - Ekinci, Serkan; Celik, Fahri; Guner, Mesut (UNIV ZAGREB FAC MECHANICAL ENGINEERING & NAVAL ARCHITECTURE, 2010)
The article presents an analysis procedure that includes noise prediction for marine propellers. As analysis of the propellers is carried out using a lifting surface method, noise prediction due to the blade sheet cavitation is taken into account using a semi-empirical formula for low frequencies. Using this procedure, an application is performed for a conventional propeller model (DTMB 4148), and noise levels of the propeller are compared with the values proposed by ICES (International Council for Exploration of the Sea). In addition, two different propellers (DTMB 4119 and Seiun-maru HSP) are analyzed by lifting surface and CFD methods; the results are compared with those of the Hoshino panel method and experimental ones. It can be concluded that the present approach provides easy, fast and reliable solutions for noise analysis with low cost and time for propeller pre-design.
Keywords: propeller analysis; lifting surface; noise prediction; sheet cavitation; CFD; SURFACE SINGULARITY; FLOW; Engineering